Schrödinger API - web service for solving multidimensional time-independent Schrödinger equation using Hermite DVR approach - Koteska, Bojana; Pejov, LJupcho; Mishev, Anastas (Faculty of Computer Science and Engineering, Skopje, North Macedonia, 2021)
Numerous phenomena taking place in the nano-world are inherently quantum in nature. Their description and, more important, quantitative treatment, therefore, requires usage of the apparatus of quantum mechanics. The basic paradigm of today’s “mainstream” quantum mechanics is the Schrödinger equation. The effort required to solve the Schrödinger equation is heavily dependent on the dimensionality and complexity of the problem itself. Here, we present the Schrödinger API - RESTful web service that provides methods for solution of one-dimensional, two-dimensional and three-dimensional time independent Schrödinger equation based on the the Gauss-Hermite Discrete Variable Representation (DVR) approach. Simple use is ensured thanks to the REST architectural style that uses HTTP requests to access and use data through the website https://schrodinger.chem-api.finki.ukim.mk. The application of the web service is shown by a computational physics use case. Specialists, but also nonexperts in computational chemistry or physics can use this service to support their research.